Clarification of the identity and geographic distribution of Phyllanthus claussenii and typification of two names in Phyllanthaceae (Phyllanthoideae) - Silva Lima, Vitória Raquel; Ribeiro Mendes, Jone Clebson; Maria Athiê-Souza, Sarah (Phytotaxa, 2024)
Phyllanthus claussenii is one of the most frequently mentioned species of Phyllanthus sect. Phyllanthus subsect. Clausseniani in various studies. However, it is often mistaken for P. subemarginatus in most collections. In the present work, we present a clarification of the identity and geographic distribution of P. claussenii and the typification of Phyllanthus acuminatus and Savia sessiliflora. The proposal of lectotypes for P. acuminatus and S. sessiliflora will enable the accurate identification of the species and avoid potential ambiguity. To achieve this, protologues and type specimens, including digital images, were analyzed, along with specimens from collections of national and international herbaria.